ARMAGEDDON ON MY SLEEVE. - ODDEN, JONATHAN (Artforum International)
The article examines the cultural and media dynamics surrounding AI wearable technology advertising, focusing on the 2025 Friend.com campaign in New York City and its historical parallel in the 1980s Winkie "Computer Friend Chip" promoted by entrepreneur Lawrence Lin (aka Dr. Winkie). Both campaigns featured enigmatic devices marketed as high-tech companions but were met with public skepticism, confusion, and critique, highlighting recurring themes of media hype, surveillance capitalism, and the spectacle of self-entrepreneurship. The 1985 video art project Media Hostages by Chip Lord, Branda Miller, and Antonio Muntadas documented the Winkie billboard endurance contest, offering a critical lens on neoliberal labor and media spectacle that resonates with contemporary AI debates. By situating current AI anxieties within this historical context, the article suggests that media panic around technology often repeats itself, and artistic reflection can provide a means to process and historicize these cycles beyond polarized hype and doom.